Exploring the Use of Microsoft PowerPoint for Early Childhood Education: A Community Engagement Program - Leni Yuliana; Mukhtar Adinugroho; Firman Yudianto; Teguh Herlambang; Fajar Annas Susanto; Jauharotur Rihlah (Indonesian Journal of Cultural and Community Development, 2023)
In traditional early childhood education, teachers often rely on paper-based materials for teaching letters and numbers recognition, which can quickly bore young children. This study aimed to explore the use of Microsoft PowerPoint as an interactive learning media for early childhood education. Using a qualitative approach, the study involved a community engagement program in Harapan Bangsa PAUD, East Java, Indonesia, to introduce the use of Microsoft PowerPoint to teachers. Interviews, observations, and event documentation provided data for descriptive analysis. The program improved teachers' ability to experiment with new and interactive educational material, according to the findings. Community involvement programs improve early childhood education and promote the Tri Dharma Perguruan Tinggi, according to participants and the PAUD Harapan Bangsa. This study highlights the potential of using technology, specifically Microsoft PowerPoint, in early childhood education, and the importance of community engagement in promoting innovation and improving education quality.Highlights: Microsoft PowerPoint as a learning medium for preschool children Community engagement programs to explore innovative learning media ICT incorporation in early childhood education Keywords: Early childhood education, Information and Communication Technology (ICT), Learning Media, Microsoft PowerPoint, Community Engagement.